Influence of Female Labor Force, Digitalization, and Unemployment on Poverty in Central Java - Samudra, Ribka Widayati; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2026)
Poverty in Central Java Province is linked to access to employment, education, and the use of digitalization. Therefore, this study aims to analyze the influence of Female Labor Force Participation (TPAKP), Average Years of Schooling for Women (RSLP), Digital Society Index (IMDI), and Open Unemployment Rate (TPT) on poverty in Central Java. This research is based on a quantitative approach through panel data regression in 35 regions during the 2022-2024 period. The results indicate that women's labor market participation, average years of schooling for women, and digital adaptability are significant, contributing to poverty reduction. Conversely, unemployment is significant and exacerbates poverty. These findings emphasize the importance of inclusive development through strengthening women's roles, equitable access to education, expanding digital literacy, and creating productive employment opportunities as sustainable strategies for poverty reduction in Central Java.